Study of spin pumping through α-Sn thin films - Gladzcuk, L; Gladczuk, L; Dluzewski, P; van der Laan, G; Hesjedal, T (Wiley, 2021)
Elemental tin in the α-phase is an intriguing member of the family of topological quantum materials. In thin films, with decreasing thickness, α-Sn transforms from a three-dimensional (3D) topological Dirac semimetal (TDS) to a two-dimensional (2D) topological insulator (TI). Getting access to and making use of their topological surface states is challenging and requires interfacing to a magnetically ordered material. Here, we report the successful epitaxial growth of α-Sn thin films on Co, forming the core of a spin-valve structure. We carried out time- and element-selective ferromagnetic resonance experiments to investigate the presence of spin pumping through the spin-valve structure. We applied a rigorous statistical analysis of the experimental data using a Landau-Lifshitz-Gilbert-Slonczewski equation based model. A strong exchange coupling contribution was found, however no unambiguous proof for spin pumping. Nevertheless, the incorporation of α-Sn into a spin-valve remains a promising approach given its simplicity as an elemental TI and its room temperature application potential.